2023
DOI: 10.1097/cji.0000000000000469
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Is Associated With Immune Checkpoint Inhibitor Efficacy and Immune-related Adverse Event Severity in Lung Cancer Patients: A Prospective Cohort Study

Abstract: Vitamin D (VitD) is potentially immunomodulatory, so here we aimed to explore the relationships between serum VitD levels, immune checkpoint inhibitor (ICI) efficacy, and immunerelated adverse events (irAEs). Serum 25-hydroxyvitamin D [25 (OH)D] levels were quantified before and after ICI treatment in prospectively enrolled patients with advanced lung cancers. Of 77 enrolled patients, 29 developed 42 irAEs. Baseline 25(OH)D levels of partial response (PRs) patients were significantly higher than non-PR patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The main current IO approaches in ICI support outlined in Fig. 1 include a Mediterranean-style diet with over 20 g of fibre [12 ••, 50••], regular exercise [14], the use of live biotherapeutics [82][83][84], ensuring vitamin D repletion [13,97], and minimising PPI and antibiotic use [67,[74][75][76], with many other integrative oncology approaches under study. This area is ripe for further research, ranging from dietary intervention and dietary component studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main current IO approaches in ICI support outlined in Fig. 1 include a Mediterranean-style diet with over 20 g of fibre [12 ••, 50••], regular exercise [14], the use of live biotherapeutics [82][83][84], ensuring vitamin D repletion [13,97], and minimising PPI and antibiotic use [67,[74][75][76], with many other integrative oncology approaches under study. This area is ripe for further research, ranging from dietary intervention and dietary component studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research around ICIs and nutritional supplements has focused on vitamin D so far with its established immunomodulatory role [96]. A prospective study of 77 patients with advanced lung cancer showed that baseline 25-hydroxy-vitamin D levels were associated with ICI response and prognosis in terms of overall survival, with a relatively low baseline vitamin D level of 40 nmol/l and above carrying an AUC of 0.63 (p = 0.047) for partial ICI response [97]. This 25-hydroxy-vitamin D level would not be considered sufficient for osteoprotection where a minimum of 50 nmol/l is usually used a cutoff [98].…”
Section: Nutritional Supplementsmentioning
confidence: 99%